Design anaylysis and fabricate robotic arm part for robotic arm car - Mohd Hussin, Amirul Hussaini (2025)
The title of this project is design and manufacture robot arm parts for robot arm cars. The theme for this project is to focus on the kindergarten and the kindergarten environment so that this robotic arm car can help teachers in terms of hygiene where this robotic arm car can help teachers pack things or toys in the kindergarten. For this project, my study focuses on the robotic arm which is an important part of the robotic arm car. In addition, the objective of this project is to design analysis and fabricate a robotic arm capable of reaching and lifting light objects. In addition, with collaboration with teammates who are responsible for ensuring that each part is able to function and move well. To produce a robotic arm is not an easy matter because there are several challenging processes, among which is choosing dimensions that are suitable for the kindergarten environment, the movement of the arm whether can turn forward or backward and the precision of the robotic arm movement to perform the task. The prototype produced has 3DOF for movement and is able to move according to the instructions given and successfully lift light items.